Platelet‐rich plasma and stromal vascular fraction cells for the engineering of axially vascularized osteogenic grafts. (24th October 2020) - Ismail, Tarek; Lunger, Alexander; Haumer, Alexander; Todorov, Atanas; Menzi, Nadia; Schweizer, Thierry; Bieback, Karen; Bürgin, Joel; Schaefer, Dirk J.; Martin, Ivan; Scherberich, Arnaud
Abstract: Avascular necrosis of bone (AVN) leads to sclerosis and collapse of bone and joints. We have previously shown that axially vascularized osteogenic constructs, engineered by combining human stromal vascular fraction (SVF) cells and a ceramic scaffold, can revitalize necrotic bone of clinically relevant size in a rat model of AVN. For a clinical translation, the fetal bovine serum (FBS) used to generate such grafts should be substituted by a nonxenogeneic culture supplement. Human thrombin‐activated platelet‐rich plasma (tPRP) was evaluated in this context. SVF cells were cultured inside porous hydroxyapatite scaffolds with a perfusion‐based bioreactor system for 5 days. The culture medium was supplemented with either 10% FBS or 10% tPRP. The resulting constructs were inserted into devitalized bovine bone cylinders to mimic the treatment of a necrotic bone. A ligated vascular bundle was inserted into the constructs upon subcutaneous implantation in the groin of nude rats. After 1 and 8 weeks, constructs were harvested, and vascularization, host cell recruitment, and bone formation were analyzed. After 1 week in vivo, constructs were densely vascularized, with no difference between tPRP‐ and FBS‐based ones. After 8 weeks, bone formation and vascularization was found in both tPRP‐ and FBS‐precultured constructs. However, the amount of bone and the vessel density were respectively 2.2‐ and 1.8‐fold higher in the tPRP group. Interestingly, the density of M2, proregenerative macrophages was also significantly higher (6.9‐fold) following graft preparation with tPRP than with FBS. Our findings indicate that tPRP is a suitable substitute for FBS to generate vascularized, osteogenic grafts from SVF cells and could thus be implemented in protocols for clinical translation of this strategy towards the treatment of bone loss and AVN.